Examining a stage-based intervention and predictors of exercise behavior among Iranian sedentary adolescents - Ghiami, Zeinab; Soh, Kim Geok; Omar Fauzee, Mohd Sofian; Soh, Kim Lam (Australian International Academic Centre, 2015)
This study evaluated the effect of an intervention based on Transtheoretical Model on exercise behavior and examined TTM constructs as predictors of stages of change among Iranian adolescents. Fifty-six sedentary adolescents completed an assessment at baseline, 2 months, and 4 months. Repeated measures ANOVA and logistic regression were used to analyze the data. The analysis showed a statistically significant difference in the mean scores on stages of change for the experimental group. Thus, students in the experiment group significantly improved their stages compared to the baseline. Furthermore, stages of change were found to correlate with TTM constructs, and self-efficacy was shown to be a strong predictor of stages of change. This study indicated that a stage-based intervention using TTM constructs could effectively improve adolescents’ intention to engage in physical activity. Moreover, the level of physical activity in adolescent can be improved by increasing their self-efficacy to exercise.